Evaluation of chilling injury in bananas using backscattered laser imaging - Hashim, Norhashila; Janius, Rimfiel; Abdul Rahman, Russly; Osman, Azizah; Shitan, Mahendran; Zude, Manuela (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The change in backscattering parameters during the appearance of chilling injury in bananas was investigated. Bananas were stored at a chilling temperature for two days and the degrees of the chilling injuries that appeared were measured before, during and after storage using backscattering imaging and visual assessment. Laser lights at 660 nm and 785 nm wavelengths were shot consecutively onto the samples in a dark room and a camera was used to capture the backscattered lights. Plots of light intensity of the images against pixel count provided a backscattering profile which contained useful information on backscattering parameters such as inflection point (IP), slope after inflection point (SA), full width half maximum (FWHM) and saturation radius (RSAT). Results indicated that there were significant changes in backscattering parameters as chilling injury developed.